Nanoemulsions - Properties, Fabrications and Applications 2019
DOI: 10.5772/intechopen.84369
|View full text |Cite
|
Sign up to set email alerts
|

In vitroAntimicrobial Activity Evaluation of Metal Oxide Nanoparticles

Abstract: In recent years, infectious diseases, specifically those that are caused by pathogens, have seen a dramatic proliferation due to resistance to multiple antibiotics, opening the colony by opportunistic pathogens. Nanotechnology and tissue engineering have been applied in the development of new antimicrobial therapies, capable of fighting opportunistic infections. In the medical field, research on antimicrobial properties of metal oxide nanoparticles have emerged to find new antimicrobial agents as an alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 58 publications
(82 reference statements)
0
25
0
Order By: Relevance
“…Effects on membrane permeability and membrane-associated key enzymes including the proton F O F 1 -ATPase can be main mechanisms of Ag NPs (Gabrielyan and Trchounian 2019). Formation of complexes of nucleic acid with heavy metals is due to impaired DNA stabilizing and bacterial viability (Sondi and Salopek-Sondi 2004;Vega-Jimenez et al 2019). Ag does not affect the cells' DNA directly; however, it increases the number of intracellular free radicals that reduce the concentration of intracellular active oxygen compounds (Sondi and Salopek-Sondi 2004;Bhabra et al 2009;Wu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Effects on membrane permeability and membrane-associated key enzymes including the proton F O F 1 -ATPase can be main mechanisms of Ag NPs (Gabrielyan and Trchounian 2019). Formation of complexes of nucleic acid with heavy metals is due to impaired DNA stabilizing and bacterial viability (Sondi and Salopek-Sondi 2004;Vega-Jimenez et al 2019). Ag does not affect the cells' DNA directly; however, it increases the number of intracellular free radicals that reduce the concentration of intracellular active oxygen compounds (Sondi and Salopek-Sondi 2004;Bhabra et al 2009;Wu et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ag does not affect the cells' DNA directly; however, it increases the number of intracellular free radicals that reduce the concentration of intracellular active oxygen compounds (Sondi and Salopek-Sondi 2004;Bhabra et al 2009;Wu et al 2013). It was also assumed that interaction of Ag ions with ribosomes led to inhibition of enzymes and protein expression necessary for ATP production (Gurunathan et al 2014;Bhabra et al 2009;Vega-Jimenez et al 2019). The mechanism of antibacterial effects of Ag NPs are still not clearly understood, but some studies have shown that Ag NPs may attach to the negatively charged bacterial cell wall and cleave it, which leads to protein denaturation and cell death (Sondi and Salopek-Sondi 2004;Wu et al 2013;Chandran et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These processes ultimately result in the disruption of the bacterial cell membrane structure, leading to cell death [ 2 , 3 ]. Recent studies have demonstrated that bacterial pathogens are exhibiting resistance against a variety of antibiotics [ 4 ], thereby limiting the effectiveness of these agents [ 5 ]. Contrary to the modes of action of antibiotics, bacterial strains are able to express antimicrobial resistance by: (1) altering the target of antibiotics by expressing genes that code for an alternate version of the antibiotic target [ 6 , 7 , 8 ]; (2) developing enzymes that can degrade or modify the drug [ 1 , 8 ]; (3) ensuring reduced uptake of antimicrobial drugs or acting as efflux pumps that push out the drugs [ 3 , 6 ]; and (4) formation of biofilm layers around the bacterial cell, thus limiting or reducing its exposure to antibiotics [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%